Outcome of Patients with Preformed Donor-Specific Antibodies Following Alemtuzumab Induction and Tacrolimus Monotherapy - Michelle Willicombe; Paul Brookes; Eva Santos‐Nunez; Jack Galliford; A. Ballow; A. McLean; Candice Roufosse; H. Terence Cook; Anthony Dorling; Anthony Ν. Warrens; Tom Cairns; David Taube (2011)
It has been shown that low-level preformed donor-specific antibodies (DSAbs) detected by luminex beads in the setting of a negative CDC and flow cytometry crossmatch (CDC/FCXM) are associated with inferior allograft outcomes. The relevance of preformed DSAbs in patients receiving alemtuzumab induction and tacrolimus monotherapy has not been studied. Four hundred and eighty renal transplant recipients with a negative CDC/FCXM had their pretransplant sera retrospectively screened for DSAbs. 45/480 (9.4%) of patients were found to have preformed DSAbs. Females and patients receiving regrafts were more likely to have a DSAb (p = 0.008 and p < 0.0001, respectively). Patients with DSAbs had inferior allograft survival (p = 0.047), increased incidence of antibody-mediated rejection (p < 0.0001) and inferior allograft function at 6 months posttransplant (p = 0.017). Patients with HLA class I DSAb (alone or in combination with a Class II DSAb) with high mean fluorescence intensities (MFIs) were at highest risk. We conclude that patients with preformed DSAb are at high risk of adverse outcomes when receiving a minimal immunosuppressive regime incorporating alemtuzumab induction. Patients found to have a preformed DSAb despite a negative crossmatch might benefit from augmented immunosuppression.